Risk Factors Associated with Sexually Transmitted Infections among Pre-Exposure Prophylaxis Users in an Urban Multi-Clinic Healthcare System. (4th October 2017) - Abrams-Downey, Alexandra; Ventuneac, Ana; Duah, Bianca; Aracena, Joaquin; Arroyo, Hansel; Aberg, Judith; Cespedes, Michelle
Abstract: Background: While the efficacy of Pre-Exposure Prophylaxis (PrEP) in the prevention of HIV is well established in clinical trials, its utility in clinical practice needs to be defined. In contrast to lifelong HIV treatment, the use of PrEP should be only for those who remain at continued risk of HIV infection. Using sexual transmitted infection (STI) diagnosis as an indicator of continued high-risk sexual behavior, this study aimed to evaluate risk factors associated with STIs in PrEP users in New York City. Methods: This retrospective cohort study included electronic health records of patients who initiated PrEP at Mount Sinai Health System from 2013 to 2016. Patients were screened for syphilis and urethral, rectal and pharyngeal gonorrhea and chlamydia every 6 months with additional testing at providers' discretion. Results: During the study period, 599 patients (95% male) initiated PrEP at 34.3 years of age on average (SD=9.8; range=17–75). Of the 516 with information on sexual orientation, 91% was MSM; 38% was White, 17 % Hispanic, and 12 % Black. Nearly 35% of the 450 tested for STIs had at least one STI with 9% receiving 3 or more positive results. A total of 278 STIs were detected over 460 person-years of follow-up among 328 patients with a known PrEP initiation date; STI incidence was 59.7/100 person-years (95% CI: 48.68–70.63). There were no significant differences by race or ethnicity. Rectal STIs were significantly higher among those aged 25–30 ( P < .01) than the other age groups and among those with PrEP-AP or Medicaid insurance coverage ( P < .05) compared with private insurance. A greater number of men who reported alcohol or drug use tested positive for STIs than men who did not report substance use ( P < .05). Adjusted logistic regression analysis showed the odds of being diagnosed with any STI or a rectal STI were 1.78 (95% CI: 1.14–2.77) and 2.56 (95% CI: 1.30–5.05) times among those reporting substance use. Conclusion: STI incidence, including rectal STIs, was significantly higher among men who reported alcohol or drug use. This study highlights a group within this cohort of PrEP users that remain at high risk for HIV and would benefit from continued adherence to PrEP as well as enhanced counseling on substance use and reducing high-risk sexual behaviors. Disclosures: All authors: No reported disclosures.